Germany : Technical Note on Banking Sector Structure. (IMF Staff Country Reports; Country Report ;, 2011)
This Technical Note focuses on banking sector structure in Germany. Germany's banking system comprises three 'pillars'-private commercial banks, public sector banks, and cooperative banks-distinguished by the ownership structure and business orientation. The German banking system includes a large number of institutions in both absolute and relative terms. This note describes the evolution of Germany's three-pillar banking system. It analyzes capitalization, credit and the intermediation of savings, and bank profitability and efficiency. It also examines the benefits of public involvement and governance in the banking system.